Computer simulation of junior gymnasts' training process - Khudolii, O. M.; Ivashchenko, O. V.; Iermakov, S. S.; Rumba, O. G. (Science of Gymnastics Journal, 2016)
The purpose of the research is to develop methodological approach to creation of an algorithm of informational provisioning of children`s and adolescents` training of motor actions. The research was conducted in compliance with a plan of factorial experiment of 22 type. The received materials were used for simulation of gymnast training process. At initial stage of training, we analyzed 530 sessions (92 gymnasts of 7-10 years old age). At the stage of basic training, we analyzed 580 trainings (78 gymnasts of 11-13 years old age). For determination of different training modes` influence on change of functional state of cardio-vascular and nervous-muscular systems we conducted a five-year longitudinal prospective research (60 gymnasts). We produced an algorithm of informational provisioning of child and adolescent training to motor actions. The algorithm is based on computer simulation of a training process. We found that the progress in fulfillment of exercise depends statistically significantly on the group of following indicators: level of fitness, organization of load and orientation of training. We provide data about change of training results and pulse frequency. We show that factorial experiment`s results were reliable and effective in determination of different working modes` influence on functional state and gymnast ability for mastering of motor actions. Algorithm of calculation of normative loads for gymnasts was worked out. The offered algorithm of computer simulation of training process`s simulation permits receiving new information about fitness, organization of load and orientation of training influence on effectiveness of motor skill formation. http://www.fsp.uni-lj.si/ads/util/mma_bin.php?id=20161026155127